PENGARUH PENERAPAN MODEL SSCS (SEARCH, SOLVE, CREATE, AND SHARE) BERBASIS GAMIFIKASI TERHADAP PEMAHAMAN KONSEP FISIKA SISWA (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the implementation of the gamification-based Search, Solve, Create, and Share (SSCS) learning model on students' understanding of physics concepts at MAN 4 Pidie. The main problem behind this study is the low level of student engagement and procedural understanding of concepts in physics subjects. The research method used is a quasi-experimental with a Non-equivalent Control Group Design. The research sample consisted of 60 students divided into an experimental class (n = 30) and a control class (n = 30). The research instrument used a concept understanding test in the form of validated reasoned multiple-choice questions. The results of data analysis showed that the average post-test score of the experimental class reached 86.4, significantly higher than the control class of 70.2. Hypothesis testing using the Independent Sample T-Test produced a significance value of 0.000 (<0.05), which means there was a real effect of the treatment given. The improvement in student abilities in the experimental class was in the High category with an N-Gain value of 0.76, while the control class was in the medium category (0.48). The integration of gamification elements such as a point system and leaderboard was proven to be effective in increasing intrinsic motivation and retention of students' conceptual understanding. The conclusion of this study is that the gamification-based SSCS model is very effective in improving the quality of physics learning at the Madrasah Aliyah level.